Parasitic protozoa of cyprinid fishes: protozoa of the roach Rutilus rutilus (Linnaeus, 1758) in Czechoslovakia - Kepr, T (Folia parasitologica, 1991)
In the years 1985-1988, a total of 254 specimens of the roach, Rutilus rutilus, captured in 23 localities of South Bohemia, were examined for the presence of protozoan parasites. Only 17 specimens (6.7%) were free of infection, whereas the others were infected at least with one parasite species, mixed infections were observed most frequently. The following species were found rarely: Myxidium rhodei Léger, 1905 in the liver and muscles. Pleistophora mirandellae Vaney et Conte, 1901 in ovaries, Trichodina nemachili Lom, 1960 on the skin, Trichodina prowazeki Grupcheva et Lom, 1980 on the skin (the first finding in Czechoslovakia). The data concerning localization of individual parasites and their prevalence are presented and five protozoan species described in detail.
Keywords: Liver; játra; Gills; Eukaryota; Intestines; Czechoslovakia; žábry; Československo; Gallbladder; mozek; protozoální infekce zvířat; Cyprinidae; močové ústrojí; protozoální infekce; slezina; střeva; Protozoan Infections, Animal; žlučník; Brain; ženské pohlaví; zvířata; nemoci ryb; Urinary Tract; Skin; ovarium; Ovary; Protozoan Infections; Fish Diseases; Female; Spleen; kůže; Animals